2008
DOI: 10.1007/s00253-008-1501-7
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia–methane two-stage anaerobic digestion of dehydrated waste-activated sludge

Abstract: The study investigated methane production from dehydrated waste-activated sludge (DWAS) with approximately 80% water content under thermophilic conditions. The repeated batch-wise treatment of DWAS using methanogenic sludge unacclimated to high concentrations of ammonia, increased the ammonia production up to 7,600 mg N per kilogram total wet sludge of total ammonia concentration, and stopped the methane production. Investigation revealed that the loading ratio of DWAS for methanogenic sludge influences anaero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…However, this method can alleviate ammonia toxicity only to a limited range (Nielsen and Angelidaki 2008b). Other traditional physicochemical methods, based on addition of ammonium-binding ions (Kougias et al 2013), increasing the C/N ratio, dilution with water (Nielsen and Angelidaki 2008a) or striping of ammonia (Nakashimada et al 2008), have not shown any practical applicability, and they are either unrealistic or too expensive.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method can alleviate ammonia toxicity only to a limited range (Nielsen and Angelidaki 2008b). Other traditional physicochemical methods, based on addition of ammonium-binding ions (Kougias et al 2013), increasing the C/N ratio, dilution with water (Nielsen and Angelidaki 2008a) or striping of ammonia (Nakashimada et al 2008), have not shown any practical applicability, and they are either unrealistic or too expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Removal after first stage fermentation has been tested when treating abattoir, municipal and sewage sludge wastes (Resch et al, 2011, Nakashimada et al, 2008, Yabu et al, 2011. A side-stream process has been tested for slaughterhouse wastes after membrane separation at temperatures below 65 o C and pH 8.5 -9 with NaOH addition (Siegrist et al, 2005); and for the liquid fraction of chicken manure digestate under 80 o C and a vacuum pressure of 600 mbar without pH adjustment (Belostotskiy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Waste-activated sludge is usually reduced and stabilised by anaerobic digestion technology [Nakashimada et al, 2008] as in the case of wastewater treatment plant under investigation. Methane produced in anaerobic digesters is inhibited by ammonia [Percheron et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…DNRA is the main nitrate reduction pathway in anaerobic digesters and in other methanogenic environments [Percheron et al, 1999]. Unfortunately, methane production in anaerobic digesters could be inhibited by high concentration of ammonia released from wasteactivated sludge [Nakashimada et al, 2008]. Mazeas et al [2008] reported that the accumulation of ammonia nitrogen, as there is no ammonia elimination process in anaerobic condition, is a biotechnological challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation